(untitled) (Communications in Computational Physics, 2020)
The traditional DSMC method is extended to simulate three-dimensional (3D) rarefied ionization flows around spacecrafts during hypervelocity reentry. The electron mass amplification is utilized and the reaction rates involving electron are modified correspondingly. A weighting factor scheme for trace species is proposed, and its impacts on collision mechanism, the realization of chemical reactions as well as the calculations of macroscopic parameters are considered. The proposed DSMC algorithm is highly efficient in simulating weakly inhomogeneous flows, and its reliability is validated by the comparisons with aerodynamics force test of Shenzhou capsule model in low density wind tunnel, the electron number densities of RAM-C II and Stardust in rarefied transitional flow regimes. The introduction of rare species weighting factor scheme can significantly improves the smoothness of the number density contours of rare species, especially for that of electron in weak ionization case, while it has negligible effect on the macroscopic flow parameters. The ionization characteristics of the Chinese lunar capsule reentry process is analyzed for the first time at the altitudes of 80km, 85km and 90km, and the predicted communication blackout altitude agrees with the actual reentry flight data. The computation reveals that, for blunt body reentry with a speed larger than the second cosmic speed, the main ionization source is the direct collision ionization, and the electron number density is high enough to cause communication blackout in traditional rarefied flow regimes.